Determinants of Internet Financial Reporting in Indonesian Local Governments - Warsidi .; Wahyu Rizkiyaningsih; Oman Rusmana; Sukirman . (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2017)
Local Governments are expected to provide relevant information related to their finance and performance to the public through the media that is easily accessible in order to meet the principles of accountability and transparency. The financial information through internet is called IFR (Internet Financial Reporting) which is a combination between the internet multimedia capability and capacity to communicate the financial information interactively. The objective of this study is to empirically examine determinants of internet financial reporting by local government in Indonesia. This study uses five variables there are Political Competition, Size, Dependency, Wealth and Type of Local Government. The sample in this study selected with purposive sampling. Total sample in this study are 130 local governments which contain 97 regency (74,6%) and 33 municipal (25,4%). Analysis method used in this study is multiple liner regression. The result shows that political competition, size and wealth of local government have a positive influence to the internet financial reporting in Indonesia. Two other variables, dependency and type of local government do not significantly affect to the internet financial reporting in Indonesian local goverments.